Mountains and women’s struggle in Southeast Asian short stories: a case study of ecofeminism - Kameo, Yosafat Andrew Gabrian (Universitas Mulawarman, 2024)
This study aims to compare the relationship between mountains and women in two Southeast Asian short stories, namely A.A. Navis's Angin Dari Gunung and Leeyee Lim's The Mountain of Longing originated from Malaysia and Indonesia. Although mountains are mostly viewed as a place where nature thrives and a spiritual place in Southeast Asia, they also can be viewed as a place of belonging and provider, especially for women in dealing with others. Seeing this, ecofeminism is chosen and used as the lens to examine the nature-women relationship that exists in the stories. The qualitative method is added to provide the primary and secondary sources that can help analyze the relationship between the mountains and women. The result of the analysis shows a close relationship between mountains and women. It is presented in a narrative of the chaotic life the female characters deal with, with mountains as the relief provider, comfort, and new life to them. This is considered the way mountains nurture women in their way.